Anaesthesia for elite athletes. Issue 10 (9th October 2022) - Bourgonjon, Bram; Vermeylen, Kris; Tytgat, Niek; Forget, Patrice
Abstract : BACKGROUND: Sports participation has been growing rapidly since the 1960s. Anaesthesiologists are increasingly confronted with athletes in a peri-operative setting. The right choice of type of anaesthesia technique, pain management of injuries, specific physiologic adaptations of the athlete and knowledge of prohibited substances are eminent for a correct approach of this subpopulation. PURPOSE: This review aims to give an overview of athletes' specific anaesthetic management in peri-operative and postoperative settings and to guide the nonspecialised anaesthetist. METHODS: We comprehensively reviewed the literature, gathered all the information available on, and synthesised it in a narrative way, regarding preoperative evaluation, intraoperative implications and postoperative pain management of the elite athlete undergoing a surgical procedure. RESULTS: An anaesthesiologist should recognise the most common benign ECG findings in athletes like bradycardia, isolated left ventricle hypertrophy on voltage criteria and early repolarisation as normal features in the athlete's heart. Isotonic physiology typically produces four-chamber dilation. In contrast, isometric stress creates high intravascular pressure leading to left ventricular hypertrophy. Pre-operative evaluation should also identify possible consumers of performance-enhancing drugs. Intraoperative points of interest for the anaesthesiologist is mainly avoiding drugs on the prohibited list of the World Anti-Doping Agency (WADA). Postoperative and chronic pain management are still developing fields in this population. The International Olympic Committee (IOC) proposed treating acute pain with a combination of paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs), topical analgesics, injectable NSAIDs and local anaesthetics. It may be suggested that chronic pain management in elite athletes could benefit from treatment in specialised multidisciplinary pain clinics. CONCLUSION: This literature review aims to serve as a guide for the anaesthesiologist taking care of the elite athlete.